The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41436-019-0579-x
|View full text |Cite|
|
Sign up to set email alerts
|

Delivering genomic medicine in the United Kingdom National Health Service: a systematic review and narrative synthesis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 72 publications
0
38
0
1
Order By: Relevance
“…Apart from these positive assessments, studies also demonstrate that some professionals are uncertain about the value of genetic testing [ 51 , 90 ] and doubt that all patients will benefit significantly from PM [ 30 , 31 , 42 , 49 , 54 , 57 ]. In addition, Kichko et al found in their study differences in attitudes between physicians from Pennsylvania and Bavaria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from these positive assessments, studies also demonstrate that some professionals are uncertain about the value of genetic testing [ 51 , 90 ] and doubt that all patients will benefit significantly from PM [ 30 , 31 , 42 , 49 , 54 , 57 ]. In addition, Kichko et al found in their study differences in attitudes between physicians from Pennsylvania and Bavaria.…”
Section: Resultsmentioning
confidence: 99%
“…One factor that could limit access to PM might be the lack of coverage by health insurance companies for medication [ 54 ], tests [ 29 , 80 ] or genetic counselling [ 90 ] and the inability of patients to pay for PM out of pocket [ 73 , 90 , 97 ]. Physicians are described as gatekeepers and their decisions on medical appropriateness, which may vary and be determined by guidelines [ 29 ], condition access to PM interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In neonatal encephalopathy, even if rWGS is ordered promptly and performed rapidly in the context of a regional ICU with a full complement of pediatric subspecialists experienced in newborn genomic medicine, a molecular diagnosis may be made too late to improve outcomes. To decrease newborn morbidity and mortality optimally, we suggest that rWGS must be implemented within a comprehensive system for rapid delivery of precision medicine (CRPM) (Stark et al 2018;Pearce et al 2019). As rWGS gains broader use in infants in ICUs worldwide, such a CRPM system will be particularly needed in hospitals lacking the full complement of pediatric subspecialists, including neurologists or medical geneticists experienced in CRPM.…”
Section: Discussionmentioning
confidence: 99%
“…This might be achieved through the improvement of literacy of healthcare professionals and citizens ( Etchegary and Wilson, 2013 ; Calabrò et al, 2020 ). Increasing citizens’ literacy requires not only specific initiatives aimed at the appropriate and conscious utilization of the new “omics” technologies but also correct information of users, for example, on the direct-to-consumer genetic tests (DTC-GTs) ( Pearce et al, 2019 ; Hoxhaj et al, 2020 ; Pastorino et al, 2021 ). Educational initiatives are therefore needed to allow citizens to acquire correct and reliable information on both the benefits and possible risks of PM in order to make appropriate health decisions supported by healthcare professionals ( Ricciardi and Boccia, 2017 ) and to become active players in the decision-making process ( Etchegary and Wilson, 2013 ), as already highlighted in the Vision Paper on Personalised Medicine Research and Implementation by 2030 from the International Consortium for Personalised Medicine (ICPerMed) ( International Consortium for Personalised Medicine, 2019 ).…”
Section: Introductionmentioning
confidence: 99%